Novel 5,6-diphenyl-1,2,4-triazine-3-thiol derivatives as dual COX-2/5-LOX inhibitors devoid of cardiotoxicity - Saraf P.; Nath Tripathi P.; Kumar Tripathi M.; Tripathi A.; Verma H.; Kumar Waiker D.; Singh R.; Kumar Shrivastava S. (My University, 2025)
A novel series of 5,6-diphenyl-1,2,4-triazine-3-thiol derivatives were designed, synthesized, and screened for their inhibitory potential against COX-2 and 5-LOX enzymes. The compounds from the series have shown moderate to excellent inhibitory potential against both targets. Compound 6k showed the inhibitions against COX-2 (IC50 = 0.33 ± 0.02 μM) and 5-LOX inhibition (IC50 = 4.90 ± 0.22 μM) which was better than the standard celecoxib (IC50 = 1.81 ± 0.13 μM) for COX-2 and zileuton (IC50 = 15.04 ± 0.18 μM) for 5-LOX respectively. Further investigation on the selected derivative 6k in rat paw edema models revealed significant anti-inflammatory efficacy. Compound 6k has also shown negligible ulcerogenic liability as compared to indomethacin. Moreover, in vivo biochemical analysis also established the compound's antioxidant properties. Compounds 6c and 6k were also observed to be devoid of cardiotoxicity post-myocardial infarction in rats. The molecular docking and dynamics simulation studies of the most active derivative 6k affirmed their consentient binding interactions with COX-2 specific ravine and cleft of 5-LOX. © 2022